Bacillus thuringiensis growth, sporulation and δ-endotoxin production in oxygen limited and non-limited cultures - Avignone Rossa, Claudio Adolfo (1992)
The production of crystals and spores of Bacillus thuringiensis var. israelensis was studied under different aeration conditions. The results with 4 l batch cultures showed that for O2 non-limited, cultures cell yield, toxin production and spore count were constant for all oxygen transfer rates (OTR). Under O2 limitation, δ-endotoxin concentrations and spore counts were lower than those obtained in non-limited cultures. In addition, δ-endotoxin yields diminished under O2 limitation, suggesting that the toxin synthesis mechanism could have been affected.